The impact of speculation on precious metals futures markets. (June 2015) - Bosch, David; Pradkhan, Elina
Abstract: Existing research finds little evidence that speculative activity in futures markets has any impact on precious metals׳ spot prices. We examine whether speculators׳ positions predict returns and return volatility in precious metals futures markets. We use two proxies for speculative activity: non-commercial traders and money managers. Money managers are a subcategory of non-commercial traders that is associated with professional speculators. Our analysis distinguishes between short- and long-term dynamics. Whereas we cannot confirm any short-term impact of speculators on returns and conditional volatility in the period after 2006, the weekly changes in non-commercial traders׳ positions appear to have a destabilizing impact on subsequent conditional volatility in gold, silver, and palladium futures markets in the period prior to June 2006. Moreover, we cannot rule out a long-term, potentially destabilizing, impact on returns when accumulated positions of speculators over monthly horizons are considered. Highlights: We examine the price impact of speculators in precious metals futures markets. We find no short-term price impact in the 2006–2013 period. By contrast, there is a long-term impact on returns for monthly horizons. The impact on conditional volatility is destabilizing before 2006 in most markets.